A measurement based Study on the Electromagnetic Radiation and its Effect in Hebron District - Khdoor, Mutasem; Shrouf, Ahmad; Manasra, Mohammad (جامعة بوليتكنك فلسطين - اتصالات, 2011)
Many studies were published all over the world discussed the side effects of electromagnetic fields (EMFs) related to different electric usage, but we did not get a confirm and a clear evidence or a negative sign about the relation between several disease and electromagnetic radiation sources especially cancer, leukemia, skull, eye tissue, skin and heart. This project represents a trail to have a global look for different kinds of electromagnetic sources which human were exposed during their daily life indoors and outdoors in Hebron district and indicate the biggest threat EM source based on real and practical measurements. Measurements have been done using high sensitive instruments; spectrum analyzer model 2650, EMR-21C field meter, personal navigator GPS and high specification Lab top. These instruments were connected and matched to gather with a software program designed to capture measurements automatically on a regular or different times according to our requirements. The spectrum analyzer is adjusted to operate at the appropriate center frequency and bandwidth that used by each source individually with different scenarios and cases; for The purpose of measuring the electric field at this center frequency and power level at the adjusted band. Also, the field meter is used to measure the electric field, magnetic field and power density. The measured values by these instruments are compared with the international Standards and limits for human exposure. The first measurements concentrate on GSM where measurements have been taken for the radiation sources on GSM system; the base stations and mobile phones. For the results of base stations measurements, we found that their level of radiation is low, where the maximum measured level at near field was about 0.475 W/m2, which was measured from Ein Sarh site at distance 3 m away from the cell antenna of the base station. It is lower than the allowed international value by 9 times. However, the average measured value was 0.0226W/m2 and lower by 200 times from the allowed value. While, the results of mobile phone measurements were greater in compare with base stations measured values where the maximum value was 2.9 W/m2 and it is less than the allowed values of IEEE and ICNIRP by 1.5 times and 2 times less than the FCC guideline. The measurement proves that the radiation from the mobile increased when we go away from the base station. In this case, the control signals of the GSM systems control the radiated power from the mobiles and increase their level to make a good connection link with the base station. Another study was made by measuring the broadcasting stations; FM radio stations and TV stations. For the measurements of the FM radio stations, the maximum power density was equal to 0.1321 W/m2, which is lower than the standards by 15 times, and the average power density of the all measurements was about 0.05 W/m2 and lower by 40 times from the international standards. However, for TV stations, the measurements show that the maximum power density measured 0.0025 W/m2, which is the least one from the whole of the maximum measured values. The last mesurements section was for Microwave Ovens, the maximum measured value for the microwave power radiation equal to 1.988 W/m2, which is lower than the international allowed levels by 5 times . This value is the highest level of radiation by comparing it with the other sources of EM radiation.
no of pages 105 , 25086, اتصالات 4/2011 , in the store
Keywords: Electromagnetic Radiation